Exploring Boarding School EFL Teachers' Strategies to Build Up Students' Speaking Competence - Hafez Al Assad; Farida Repelita Waty Br. Kembaren; Muhammad Dalimunte (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study investigates how EFL (English as a Foreign Language) teachers utilize teaching strategies to enhance students' speaking competence, particularly in Grade 8 classes. The data were collected through 30-minute observations per teacher and 15-minute semi-structured interviews with both teachers from the boarding school, conducted both inside and outside the classroom. This study employed a descriptive case study approach, and the data were analyzed using descriptive qualitative analysis to identify recurring patterns and categorize the strategies used in the classroom. The findings revealed that teachers employed a combination of strategies both inside and outside the classroom. Inside the classroom, strategies include vocabulary drilling, question-and-answer sessions, discussions, and group work. Meanwhile, the teachers from outside the classroom employed a range of teaching strategies, including group work, vocabulary drilling and memorization, as well as question-and-answer sessions and conversations. The above strategies demonstrate that interaction strategies, such as dialogue, conversation, and Q&A, encourage the use of speaking language, while vocabulary drilling provides the foundation for speaking development. The results offer insight into how boarding schools can promote lifelong language learning by striking a balance between classroom instruction and additional practice. The study highlights the practical value of interactive strategies in fostering speaking competence. However, as the research was limited to two teachers in a single institution, the findings provide transferable insights for similar EFL boarding school settings, particularly in highlighting the practical value of interactive approaches for fostering speaking competence.